Development of glass-ceramic scintillators for gamma-ray astronomy. (May 2015) - de Faoite, D; Hanlon, L; Roberts, O; Ulyanov, A; McBreen, S; Tobin, I; Stanton, K T
Abstract: Scintillators synthesised as glass-ceramics have several potential benefits compared to the currently-used halide scintillators, including non-hygroscopicity, mechanical ruggedness, ease of producing customisable shapes, and the potential for low-cost synthesis. The use of these scintillators is considered for a gamma-ray telescope operating in the 0.2MeV-50MeV photon range. Inorganic scintillator compounds suitable for incorporation into glass-ceramics are assessed. In addition, several families of glass suitable for use as hosts for scintillating compounds are also reviewed.